The application of homomorphism in cryptography - A. Z. Lunkes; F. Borges (Trends in Computational and Applied Mathematics)
The use of new technologies and the internet has been growing, so the privacy and security of users have be guaranteed when browsing the web. For this purpose, the encryption scheme depends on the sharing of a key between the peers involved in the exchange of a message. The concept of homomorphism was used as a possible solution for computing without the need to decipher the data.  Homomorphic Cryptography is the encryption scheme that preserves the privacy and security of encrypted data.